Mapping and monitoring bullying and violence : building a safe school climate - As?or, Ron; Benbenishty, Rami (New York : Oxford University Press, 2018)
Presents a guidebook for district and school education leaders and professionals to reduce incidents of violence and bullying and enhance students' well-being. Written in a step-by-step format, the text is designed to assist in collecting and making better use of data on non-academic issues in schools, such as reports of victimization, weapon and drug possession, theft of personal property, suicide ideation, and other areas. The authors advocate an ongoing monitoring approach that involves collecting information from multiple audiences about what is taking place in and around schools. One part of this process is mapping, which gives school leaders, students, and staff members a visual record of areas of the campus considered safe, alongside those that students view to be places where they might encounter bullying, harm, or trouble. Other common parts of such systems are surveys among students, educators, and parents. The authors include practical examples of how to design such a system, gather current information, analyze and display the data, share it with different audiences, and use it to find solutions. --From publisher description.
Introduction: The case for monitoring and mapping of school violence and bullying -- Creating awareness and making a commitment -- Examples of monitoring -- Developing a monitoring system -- What and how to monitor -- Student voice -- The voices of staff members -- The voices of parents -- Surveys -- Focus groups -- Observations -- Mapping -- Administrative records -- Photos, videos, and other technology -- Analysis and presentation -- Sharing the monitoring feedback -- Using monitoring to support and improve schools -- Conclusion: Implications for the future.
Includes bibliographical references (pages [87]-89) and index.
Keywords: Bullying in schools -- Prevention; Bullying -- Prevention; School violence -- Prevention